2004
DOI: 10.1111/j.1365-2672.2004.02192.x
|View full text |Cite
|
Sign up to set email alerts
|

National survey for Salmonella in pigs, cattle and sheep at slaughter in Great Britain (1999-2000)

Abstract: Aims: The objective of these surveys was to estimate the prevalence of faecal carriage of Salmonella in healthy pigs, cattle and sheep at slaughter, and of pig carcase contamination with Salmonella. These data can be used as a baseline against which future change in Salmonella prevalence in these species at slaughter can be monitored. Methods and Results: In this first randomized National Survey for faecal carriage of Salmonella in slaughter pigs, cattle and sheep in Great Britain, 2509 pigs, 891 cattle and 97… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
87
3
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(102 citation statements)
references
References 50 publications
8
87
3
2
Order By: Relevance
“…Although consumption of contaminated poultry meat and eggs is the primary risk factor for human nontyphoidal salmonellosis, other food-producing animals also pose a threat of zoonotic transmission. For example, serovar Typhimurium is highly prevalent in pig production, with caecal samples of 11.1 per cent of pigs testing positive for S. Typhimurium in a UKwide year-long survey in 1999-2000 (Davies et al 2004). S. Typhimurium has also been associated with lamb, beef and dairy produce, albeit low levels were recorded in the above survey.…”
Section: Human Salmonellosis and Animal Reservoirsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although consumption of contaminated poultry meat and eggs is the primary risk factor for human nontyphoidal salmonellosis, other food-producing animals also pose a threat of zoonotic transmission. For example, serovar Typhimurium is highly prevalent in pig production, with caecal samples of 11.1 per cent of pigs testing positive for S. Typhimurium in a UKwide year-long survey in 1999-2000 (Davies et al 2004). S. Typhimurium has also been associated with lamb, beef and dairy produce, albeit low levels were recorded in the above survey.…”
Section: Human Salmonellosis and Animal Reservoirsmentioning
confidence: 99%
“…For example, S. Derby was common in UK pigs in 1999-2000 (6.3 per cent of caeca and 1.6 per cent of carcasses) yet in the same period it was rarely observed in humans even though pork products are considered to be an important food vehicle of Salmonella (Davies et al 2004). Similarly, serovars Livingstone, Senftenberg, Agarna, Kedougou and Mbandaka were each responsible for 7-13 per cent of Salmonella-positive tests in chickens in 2007 (compared with 18.8 per cent for Enteritidis), yet none appear in the top 10 serovars causing human disease in the same period (http://www.defra.gov.uk/animalh/ diseases/zoonoses/zoonoses_reports/zoonoses2007.pdf).…”
Section: Human Salmonellosis and Animal Reservoirsmentioning
confidence: 99%
“…The occurrence of Salmonella in pig carcasses after processing is different from country to country. The reported percentage of the occurrence was 6% in Italy [15], 0.2% in Switzerland [16], 5.3% in Great Britain [17] and 4.7% in Germany [18] during the period from 2000 to 2003.…”
Section: Discussionmentioning
confidence: 99%
“…The agglutination test is considered the preferred method in export and diagnostic purposes for samples from all species of farm animals (Davies, 2004;OIE, 2010). Our research demonstrated the possibility of performing it alongside the analysis scheme established in the brucellosis official eradication program.…”
Section: Discussionmentioning
confidence: 99%
“…Flock diagnosis of S. Abortusovis in sheep can be performed by serological tests conducted on a statistically representative sample of the population, but results are not always indicative of active infection (OIE, 2010). These include serum agglutination test (SAT), hemagglutination inhibition, complement fixation, indirect immunofluorescence, gel immunodiffusion, and enzyme-linked immunosorbent assay (ELISA) (Davies, 2004).…”
mentioning
confidence: 99%